2018
DOI: 10.3758/s13415-018-0626-0
|View full text |Cite
|
Sign up to set email alerts
|

The brain-adipocyte-gut network: Linking obesity and depression subtypes

Abstract: Major depressive disorder (MDD) and obesity are dominant and inter-related health burdens. Obesity is a risk factor for MDD, and there is evidence MDD increases risk of obesity. However, description of a bidirectional relationship between obesity and MDD is misleading, as closer examination reveals distinct unidirectional relationships in MDD subtypes. MDD is frequently associated with weight loss, although obesity promotes MDD. In contrast, MDD with atypical features (MDD-AF) is characterised by subsequent we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 327 publications
(428 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, a study found that atypical depression is associated with chronic psycho-immuno-neuro-endocrinal dysfunction due to inflammatory, leptin-ghrelin, neuroendocrinal, and gut microbiome systems influenced by chronic image-associated psychological stress and sensitivity to rejection especially in young female patients that can lead to behavioral dysregulation in the form of hyperphagia, lethargy, and hypersomnia [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study found that atypical depression is associated with chronic psycho-immuno-neuro-endocrinal dysfunction due to inflammatory, leptin-ghrelin, neuroendocrinal, and gut microbiome systems influenced by chronic image-associated psychological stress and sensitivity to rejection especially in young female patients that can lead to behavioral dysregulation in the form of hyperphagia, lethargy, and hypersomnia [39].…”
Section: Discussionmentioning
confidence: 99%
“…These structural alterations can partly explain why obesity predisposes to psychiatric disorders development (e.g., mood disorders) and provide a theoretical frame for the association between weight status and neuropsychic functions, such as cognitive/executive functions and emotion regulation. For a more thorough examination of the mechanisms mentioned above, see the recent reviews by Stapelberg et al [9,10] and Shefer et al [8]. development and maintenance of this condition, thus lending intriguing insights to obesity medicine and representing possible targets for treatment and prevention [5,6].…”
Section: A Bidirectional Relationshipmentioning
confidence: 99%
“…It has long been known that MDD is a risk factor for obesity. Obesity, in turn, is a risk factor for MDD, and there is a bidirectional pathophysiological bond between these conditions, so that we can speak of "obesity-associated depression" and "depression-associated obesity" [10]. In particular, a metanalysis of longitudinal studies concluded that patients with obesity had a 55% increased risk of developing MDD in their lifetime, while patients suffering from MDD have a 58% risk of developing obesity [50].…”
Section: Mood Disorders and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging shreds of evidence have suggested a potential role of the gut microbiota in the pathophysiology of depression (Jiang et al, 2015;Zheng et al, 2016). However, there is limited literature which reviews the link between depression to gut microbiota by different groups of researchers (Slyepchenko et al, 2017;Patist et al, 2018;Schachter et al, 2018) (Figure 1).…”
Section: Depression In Epilepsy and The Gut-brain-axismentioning
confidence: 99%